1992
DOI: 10.1111/j.1365-2788.1992.tb00469.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone deficiency in Down's syndrome children

Abstract: Down's syndrome (DS) children have been reported to have severe postnatal growth arrest and microcephaly. To determine if growth hormone (GH) deficiency plays a role in growth retardation in DS, 20 children were studied. The subjects (13 boys, 7 girls) were aged between 15 months and 13'9 years, had a height SDS ranging from -119 to -548, weight SDS ranging from -021 to -4-58, head circumference SDS ranging from -0 40 to -66, and a skeletal age ranging from 0 9 to 4'6 SD below the mean for normal children of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 46 publications
(28 reference statements)
0
9
0
Order By: Relevance
“…Growth retardation therefore becomes pronounced during the period when GH starts to stimulate growth. There is no obvious deficiency of GH ir\ serum (Milunsky et al 1968;Ruvalcaba et al 1972;Anneren et al 1986), eveti though suboptimal endogenous GH production due to a hypothalamic dysfunction has been suggested in DS (Castells et al 1988). There is a selective deficiency of IGF-1 in sertim in patients with DS older than 2 years of age (Sara etal.…”
Section: Introductionmentioning
confidence: 99%
“…Growth retardation therefore becomes pronounced during the period when GH starts to stimulate growth. There is no obvious deficiency of GH ir\ serum (Milunsky et al 1968;Ruvalcaba et al 1972;Anneren et al 1986), eveti though suboptimal endogenous GH production due to a hypothalamic dysfunction has been suggested in DS (Castells et al 1988). There is a selective deficiency of IGF-1 in sertim in patients with DS older than 2 years of age (Sara etal.…”
Section: Introductionmentioning
confidence: 99%
“…Children with GH deficiency show reduced SSR, while patients with acromegaly have a higher SSR than healthy controls [ 21 , 23 ]. It is known that DS is associated with growth hormone deficiency [ 24 ]. In our albeit small population, children with DS and a height below the 3rd percentile showed no reduced SSR rate compared with the other children (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors reported reduction of IGF-I levels in DS patients, without any age-related differences, to an extent similar to that in GHD patients [165,[170][171][172], while others showed a progressive decrease during advacing age, although within the age-related normal range [173]. Nutritional, lifestyle and/or social differences may explain these controversial findings.…”
Section: Gh/igf-i Axis In Down's Syndrome: a Clin-ical Model Of Anticmentioning
confidence: 95%
“…Low GH response to L-DOPA and clonidine, two indirect GH-releasing agents, have been shown in prepubertal DS patients, while normal arginine-as well as GHRH-induced GH rise was reported in DS children [171][172][173][174][175][176]. Normal GH response in DS children was also observed after maximal provocative stimuli, such GHRH combined with pyridostigmine or arginine, as well as after hexarelin, a synthetic GH secretagogue mimicking ghrelin action [173,176,177].…”
Section: Gh/igf-i Axis In Down's Syndrome: a Clin-ical Model Of Anticmentioning
confidence: 99%